The Glass Is Half Full: The Need to Promote Positive Mental Health in Black College Students. Issue 4 (2nd October 2021) - Mushonga, Dawnsha R.
ABSTRACT: Background: Traditionally, research examining Black student's mental health has occurred from a deficits-based perspective while failing to acknowledge their fortitude in persevering despite enduring adverse circumstances (i.e. racism and discrimination). However, a growing body of literature highlights the importance of focusing on positive mental health (PMH), which is comprised of social, emotional, and psychological well-being. More importantly, it buffers against mental illness which is important given the low help-seeking rates among Black students.Objective: To date, no studies have examined PMH exclusively in Black students; therefore, our understanding of their ability to flourish in the college setting remains limited. Therefore, this article provides an overview of Black college students and the need to target correlates of PMH to promote mental health.Conclusion: Focusing on PMH provides a holistic picture of Black student's mental health and aids in reducing the educational and health disparities that currently exist between Black and White students.